Sonographic measurement of the fetal cerebellum, cisterna magna, and cavum septum pellucidum in normal fetuses in the second and third trimesters of pregnancy - Serhatlioglu, S; Kocakoc, E; Kiris, A; Sapmaz, E; Boztosun, Y; Bozgeyik, Z (John Wiley & Sons Inc, 2003)
Purpose. Absence of the cavum septum pellucidum (CSP), the cisterna magna (CM), or both, and enlargement of either or both structures are associated with various central nervous system malformations. In an effort to determine normal sizes and relationships between these cranial structures, we measured the CSP and CM in normal fetuses in the second and third trimesters of pregnancy using transabdominal sonography. Methods. Women with uncomplicated pregnancies and normal singleton fetuses between 16 and 38 weeks' menstrual age were included in this prospective study. The width and anteroposterior (AP) diameters of the CSP were measured on the transverse transventricular plane, and the AP diameter of the CM was measured on the transcerebellar plane from the posterior aspect of the cerebellar vermis to the inner edge of the cranium. The transverse and AP diameters of the cerebellum were also measured. In addition, we measured the biparietal diameters (BPDs). Results. In total, 130 women participated; 64 were examined in their second trimester and 66 in their third trimester. The mean age of the women was 27.4 +/- 4.8 years (range, 18-38 years), and the mean menstrual age of the fetuses was 26.9 +/- 6.7 weeks (range, 16-38 weeks). The mean BPD was 66.8 +/- 18.7 mm (range, 30-96 mm). The mean width and AP diameter of the CSP and the mean AP diameter of the CM differed significantly between the second and third trimesters (p < 0.001). All measured parameters correlated significantly with menstrual age and BPD. Conclusions. In normal fetuses, the CSP and CM should be visible on transabdominal sonography between 16 and 38 weeks' menstrual age. Because abnormalities in these cranial structures may be indicative of central nervous system malformations, the availability of mean sonographic measurements from normal fetuses should be helpful in determining the need for additional testing in fetuses with abnormal measurements. (C) 2003 Wiley Periodicals, Inc.
Keywords: cavum septum pellucidum; cisterna magna; cerebellum; fetal; measurement; normal anatomy; ultrasonography